2010
DOI: 10.1002/path.2676
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenocarcinoma cells floating in lymphatic vessels resist anoikis by expressing phosphorylated Src

Abstract: The ability to resist anoikis is critical for carcinoma cells to metastasize. Although several lung adenocarcinoma cell lines were shown to repress anoikis through the activation of Src, it remains unknown whether Src actually plays a crucial role in anoikis resistance in lung adenocarcinoma tissues. We examined 20 human lung adenocarcinoma tissues with lymphatic permeation and nine cell lines to investigate whether intralymphatic floating carcinoma cells in the tissues, used as an in vivo model of anoikis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…2 Several research groups, including us, have reported that Src, a non-receptor type tyrosine kinase, has a role in the anoikis resistance in lung adenocarcinomas. [3][4][5] We have demonstrated that 1) intralymphatic floating lung adenocarcinoma cells observed in primary tumor tissues form compact nests expressing E-cadherin and phosphorylated Src; 2) these two proteins are also expressed in tumor spheroids of four lung adenocarcinoma cell lines (LC-KJ, HCC827, H1650, and H1975) cultured in suspension, the shape of which is similar to intralymphatic tumor cell nests observed in tissues. 5 We thus consider tumor spheroids of the four cell lines in suspension culture system to be a suitable in vitro model of circulating tumor cells.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…2 Several research groups, including us, have reported that Src, a non-receptor type tyrosine kinase, has a role in the anoikis resistance in lung adenocarcinomas. [3][4][5] We have demonstrated that 1) intralymphatic floating lung adenocarcinoma cells observed in primary tumor tissues form compact nests expressing E-cadherin and phosphorylated Src; 2) these two proteins are also expressed in tumor spheroids of four lung adenocarcinoma cell lines (LC-KJ, HCC827, H1650, and H1975) cultured in suspension, the shape of which is similar to intralymphatic tumor cell nests observed in tissues. 5 We thus consider tumor spheroids of the four cell lines in suspension culture system to be a suitable in vitro model of circulating tumor cells.…”
mentioning
confidence: 79%
“…[3][4][5] We have demonstrated that 1) intralymphatic floating lung adenocarcinoma cells observed in primary tumor tissues form compact nests expressing E-cadherin and phosphorylated Src; 2) these two proteins are also expressed in tumor spheroids of four lung adenocarcinoma cell lines (LC-KJ, HCC827, H1650, and H1975) cultured in suspension, the shape of which is similar to intralymphatic tumor cell nests observed in tissues. 5 We thus consider tumor spheroids of the four cell lines in suspension culture system to be a suitable in vitro model of circulating tumor cells. In addition, we have shown that ABT-263, a potent Bcl-2 inhibitor, 6,7 significantly enhances the susceptibility for apoptosis in suspended lung adenocarcinoma cells treated with Src tyrosine kinase inhibitors (TKIs), 8 as ABT-737, the predecessor of ABT-263, can increase the levels of epidermal growth factor receptor (EGFR) TKI-induced apoptosis in EGFR-mutant lung adenocarcinomas.…”
mentioning
confidence: 79%
See 3 more Smart Citations